Applied plant genomics and biotechnology - Poltronieri, Palmiro; Hong, Yiguo (Sawston, Cambridge : Woodhead Publishing is an imprint of Elsevier, 2015)
Applied plant genomics and biotechnology reviews the recent advancements in the post-genomic era, discussing how different varieties respond to abiotic and biotic stresses, investigating epigenetic modifications and epigenetic memory through analysis of DNA methylation states, applicative uses of RNA silencing and RNA interference in plant physiology and in experimental transgenics, and plants modified to produce high-value pharmaceutical proteins. The book provides an overview of research advances in application of RNA silencing and RNA interference, through Virus-based transient gene expression systems, Virus induced gene complementation (VIGC), Virus induced gene silencing (Sir VIGS, Mr VIGS) Virus-based microRNA silencing (VbMS) and Virus-based RNA mobility assays (VRMA); RNA based vaccines and expression of virus proteins or RNA, and virus-like particles in plants, the potential of virus vaccines and therapeutics, and exploring plants as factories for useful products and pharmaceuticals are topics wholly deepened. The book reviews and discuss Plant Functional Genomic studies discussing the technologies supporting the genetic improvement of plants and the production of plant varieties more resistant to biotic and abiotic stresses. Several important crops are analysed providing a glimpse on the most up-to-date methods and topics of investigation. The book presents a review on current state of GMO, the cisgenesis-derived plants and novel plant products devoid of transgene elements, discuss their regulation and the production of desired traits such as resistance to viruses and disease also in fruit trees and wood trees with long vegetative periods. Several chapters cover aspects of plant physiology related to plant improvement: cytokinin metabolism and hormone signaling pathways are discussed in barley; PARP-domain proteins involved in Stress-Induced Morphogenetic Response, regulation of NAD signaling and ROS dependent synthesis of anthocyanins. Apple allergen isoforms and the various content in different varieties are discussed and approaches to reduce their presence. Euphorbiaceae, castor bean, cassava and Jathropa are discussed at genomic structure, their diseases and viruses, and methods of transformation. Rice genomics and agricultural traits are discussed, and biotechnology for engineering and improve rice varieties. Mango topics are presented with an overview of molecular methods for variety differentiation, and aspects of fruit improvement by traditional and biotechnology methods. Oilseed rape is presented, discussing the genetic diversity, quality traits, genetic maps, genomic selection and comparative genomics for improvement of varieties. Tomato studies are presented, with an overview on the knowledge of the regulatory networks involved in flowering, methods applied to study the tomato genome-wide DNA methylation, its regulation by small RNAs, microRNA-dependent control of transcription factors expression, the development and ripening processes in tomato, genomic studies and fruit modelling to establish fleshy fruit traits of interest; the gene reprogramming during fruit ripening, and the ethylene dependent and independent DNA methylation changes.
Transgenic, cisgenic and novel plant products : challenges in regulation and safety assessment / Palmiro Poltronieri and Ida Barbara Reca -- What turns on and off the cytokinin metabolisms and beyond / Eva Jiskrov Ivona Kubalovand Yoshihisa Ikeda -- Apple allergens genomics and biotechnology : unravelling the determinanats of apple allergenicity / Federica Savazzini, Giampaolo Ricci and Stefano Tartarini -- Non-food interventions : exploring plant biotechnology applications to therapeutic protein production / Matteo Busconi, Mariangela Marudelli and Corrado Fogher -- In planta produced virus-like particles as candidate vaccines / Slavica Mati{u28E0}and Emanuela Noris -- Biotechnology of euphorbiaceae (Jatropha curcas, Manihot esculenta, Ricinus communis) / Fatemah Maghuly, Johann Vollmann and Margit Laimer -- Regulation framework for flowering / Tiziana Sgamma and Stephen Jackson -- Epigenetic regulation during fleshy fruit development and ripening / Emeline Teyssier, Lisa Boureauv, Weiwei Chen, Ruie Lui, Charlotte Degraeve-Guibault, Linda Stammitti, Yiguo Hong and Philippe Gallusci -- Tomato fruit quality improvement facing the functional genomics revolution / Dominique Rolin, Emeline Teyssier, Yiguo Hong and Philippe Gallusci -- Rice genomics and biotechnology / Dawei Xue, Hua Jiang and Qian Qian -- Genome-wide DNA methylation in tomato / Rupert Fray and Silin Zhong -- Recent application of biotechniques for the improvement of mango research / Mohammad Sorof Uddin and Qi Cheng -- Cotton genomics and biotechnology / Hao Juan and Sun Yuqiang -- Virus technology for functional genomics in plants / Cheng Qin, Qi Zhang, Meiling He, Junhua Kong, Bin LI, Atef Mohamed, Weiwei Chen, Pengcheng Zhang, Xian Zhang, Zhiming Yu, Tongfei Lai, Nongnong Shi, Toba Osman and Yiguo Hong -- PARP proteins, NAD, epigenetics, antioxidative response to abiotic stress / Palmiro Poltronieri and Masanao Miwa -- Applied oilseed rape marker technology and genomics / Christian Obermeier and Wolfgang Friedt.
Includes bibliographical references and index.
Elsevier
Keywords: Genomics; Plant genetics; Biotechnology; SCIENCE -- Life Sciences -- Biochemistry; Biotechnology; Genomics; Plant genetics; Electronic books